Water & wastewater: Evaporation system is water off a cup's back. Issue 5 (September 2015) - Unknown
Abstract : Special EFX, was high on the agenda when developing a new water treatment plant at its facility in Stratford-upon-Avon. By installing a specialist evaporation system, process water recycling expert NHE was able to virtually eliminate the need for regular wastewater collection and disposal. The project has reduced the volume of wastewater by 90% as well as delivering overall cost savings for the plant.